Analisis Analisis Langkah-Langkah Pendekatan Acuan Patokan (PAP) Asesmen dalam Pendidikan Islam - Susilowati, Endah; Shaleh, Shaleh; Zulfatulkhoiriyah, Zulfatulkhoiriyah (Moderasi : Journal of Islamic Studies, 2024)
The Criterion-Referenced Approach (CRA) serves as an assessment methodology that evaluates students' performance by comparing their results against predetermined standards. This study aims to analyze the systematic steps involved in implementing CRA within the learning process. Utilizing a qualitative approach, this library research collects data from books, journals, scholarly articles, and documents relevant to the research variables. Data analysis is conducted through content analysis, focusing on documented information in various formats, including text, images, and audio. CRA implementation encompasses several structured steps: planning, which includes defining learning objectives, setting standards or criteria, developing assessment tools, determining success benchmarks, and conducting data collection and analysis. Following these steps ensures effective assessment outcomes. By emphasizing a comparison between students' scores and established achievement standards, CRA provides a clear evaluation of students' mastery of the learning material. The findings highlight the practical utility of CRA in designing remedial programs, tracking student progress, and measuring the achievement of learning objectives. This study underscores CRA's pivotal role in enhancing the effectiveness of assessment within educational contexts.